2013
DOI: 10.1093/annonc/mds580
|View full text |Cite
|
Sign up to set email alerts
|

Final height in survivors of childhood cancer compared with Height Standard Deviation Scores at diagnosis

Abstract: Height at diagnosis was an important determinant for height SDS at follow-up. Survivors treated with TBI, cranial and craniospinal irradiation should be monitored periodically for adequate linear growth, to enable treatment on time if necessary. For correct interpretation of treatment-related late effects studies in CCS, pre-treatment data should always be included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Additionally, survivors treated with 2,400 cGy CRT had a greater overall loss of final adult height (–1.38 Ht-SD) than those treated with 1,800 cGy (–0.65 Ht-SD) [4]. In another study of 573 Dutch CCS treated with a median CRT dose of 2,480 cGy, exposure to CRT had a significant impact on the final adult height (–0.86 Ht-SD loss) and it was a significant risk factor for short adult height, with an increased risk at higher CRT doses [5]. In addition to increasing doses of CRT, a younger age, female gender, and prepubertal status at diagnosis are risk factors for a short final adult height [4-8].…”
Section: Growth Impairment and Short Adult Height Following Exposure mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, survivors treated with 2,400 cGy CRT had a greater overall loss of final adult height (–1.38 Ht-SD) than those treated with 1,800 cGy (–0.65 Ht-SD) [4]. In another study of 573 Dutch CCS treated with a median CRT dose of 2,480 cGy, exposure to CRT had a significant impact on the final adult height (–0.86 Ht-SD loss) and it was a significant risk factor for short adult height, with an increased risk at higher CRT doses [5]. In addition to increasing doses of CRT, a younger age, female gender, and prepubertal status at diagnosis are risk factors for a short final adult height [4-8].…”
Section: Growth Impairment and Short Adult Height Following Exposure mentioning
confidence: 99%
“…CCS treated with TBI are at an increased risk for growth impairment and short adult height [5, 8, 33, 34]. For example, among 3,467 CCS of acute leukemia, those treated with TBI had significantly lower adult Ht-SD (mean Ht-SD –1) compared to those treated with no RT (mean Ht-SD –0.02) and to those treated with CRT only (mean Ht-SD –0.64) [8].…”
Section: Growth Impairment and Short Adult Height Following Exposure mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that reduced adult stature could negatively affect self-esteem, social relationships, and functioning among childhood cancer survivors [ 69 ]. In a study of 183 young survivors of childhood cancer, Mulhern, et al [ 70 ] reported a 2.3-fold (95% CI: 1.0–5.0) higher risk of school-related problems among those with physical disabilities than those without physical disabilities (including short stature), but found no association between physical disability and the activities component of the Child Behavior Checklist [ 70 ].…”
Section: Endocrine Complicationsmentioning
confidence: 99%
“…However, the standing height may not accurately depict lung function in CCS. While CCS do demonstrate overall stunting in growth, they also demonstrate a distinct thoracic growth deficiency . If CCS demonstrate relatively worse thoracic growth than appendicular growth, the result is that standing height would inappropriately overestimate predictive thoracic cavity size, which can be misleading when calculating spirometry, plethysmography, and diffusing capacity results .…”
Section: Introductionmentioning
confidence: 99%